Bronchial stenosis requires vigilance against tracheal mucormycosis: a case report - Wang, Ye; Wang, Shiyao; Zhao, Hongmei; Wang, Chen (Frontiers in Medicine, 2025)
This report highlights the importance of differentiating the etiology of dyspnea and tracheal stenosis. While acknowledging that tracheal stenosis can significantly cause respiratory distress, we emphasize the need to consider tracheal mucormycosis in the differential diagnosis, particularly in patients with risk factors such as uncontrolled diabetes and trauma. Early recognition and timely antifungal therapy remain crucial in managing this potentially fatal infection. Prioritizing early identification and treatment of mucormycosis before it progresses to the lungs can significantly improve patient outcomes and impact clinical practice.